2009
DOI: 10.1074/jbc.m109.008391
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Regulation of Matrix Extracellular Phosphoglycoprotein Expression by Bone Morphogenetic Protein-2

Abstract: Matrix extracellular phosphoglycoprotein (MEPE) is mainly expressed in mineralizing tissues, and its C-terminal proteolytic cleavage product is an acidic-serine-asparate-rich-MEPE-associated motif (ASARM) that is a strong regulator of body phosphate metabolism and mineralization. There is sufficient data supporting a role for MEPE protein function in mineralization, however, little is known about the regulation of MEPE gene expression. As bone morphogenetic protein-2 (BMP-2) is one of the most important signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 37 publications
4
46
1
Order By: Relevance
“…4D, lanes 7 and 14, asterisk). Contrary to the results with the Alp and Mepe promoters (7,14), Msx2 did not form a complex with the probes when Msx2 protein was increased, although it did inhibit Dlx5 binding to h2 (Fig. 4D).…”
Section: -G)contrasting
confidence: 51%
See 4 more Smart Citations
“…4D, lanes 7 and 14, asterisk). Contrary to the results with the Alp and Mepe promoters (7,14), Msx2 did not form a complex with the probes when Msx2 protein was increased, although it did inhibit Dlx5 binding to h2 (Fig. 4D).…”
Section: -G)contrasting
confidence: 51%
“…2C). We previously reported that Dlx5 stimulates Alp and Mepe expression, but Msx2 antagonizes the stimulatory effect of Dlx5 by competing for binding to the same response elements in promoters (7,14). On the basis of these results, we hypothesized that Msx2 also suppresses Dspp expression.…”
Section: -G)mentioning
confidence: 85%
See 3 more Smart Citations